SISTEM PENDUKUNG KEPUTUSAN UNTUK DETEKSI DINI KESEHATAN MENTAL MAHASISWA MENGGUNAKAN FUZZY SIMPLE ADDITIVE WEIGHTING - Nawindah, Nawindah (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
High mental health problems result in a decrease in academic roles, students who experience repeated trauma need to do counseling so that their potential can develop optimally, be able to overcome problems and be able to adapt in the midst of changes that often occur. The absence of routine health checks carried out by students causes the need for a way to support decision making. For this reason, a method is needed to detect the mental health level of students early with the fuzzy simple additive weighting method, the results of which can be a recommendation. Based on research conducted using 10 samples of student data who have answered the self-reporting questionnaire (SRQ-20) with different levels, namely: 5 students are recommended to have severe mental health levels, 4 students are recommended to have moderate mental health and 1 student is recommended to have moderate mental health. have a mild level of health. For students who have severe and moderate health, regular psychological consultation is needed.